New type of pathogenicity of Thelohanellus kitauei Egusa & Nakajima, 1981 infecting the skin of common carp Cyprinus carpio L. Issue 1 (February 2016) - Zhai, Yanhua; Gu, Zemao; Guo, Qingxiang; Wu, Zizhen; Wang, Hongmei; Liu, Yang
Abstract: Thelohanellus kitauei Egusa & Nakajima, 1981 is a common parasite infecting the intestine of common carp Cyprinus carpio L., resulting in mass mortality or loss of economic value of cultured carp. In the present study, T. kitauei infecting host skin was detected. The morphological, molecular and histological data of this parasite in the new organ record are presented. Morphological analysis showed the current specimen morphologically similar to T. kitauei from the intestine. Despite the spore length and polar capsule length of the current specimen larger than those of T. kitauei from the intestine, ranges of dimensions overlap, which is more suggestive of intraspecific variation than distinct species. BLAST search revealed that the present small subunit ribosomal DNA gene sequence is identical to those of T. kitauei . Histologically, most of spores distributed in the stratum spongiosum of dermis, and some spores in the strata compactum of host skin were also observed. Above all, both morphology and molecular analysis indicated that the current species from the skin of common carp is conspecific with T. kitauei from the intestine of carp and organ habitats transfer of T. kitauei from host intestine to skin may have occurred. Graphical abstract: Thelohanellus kitauei infected the skin of common carp. Highlights: Spores of present species from skin of common carp are similar to T. kitauei . The ssrDNA gene sequence of current species is identical to those of T. kitauei . Most spores of current species distributed in the stratum spongiosum of dermis. The p-distances from different sites were larger than those from same sites.